PENGUATAN DAN OPTIMALISASI FUNGSI LEMBAGA LEGISLATIF DI DAERAH - Heriyanto Heriyanto (ADMIN: Jurnal Administrasi Negara, 2023)
Strengthening and optimizing legislative institutions in the era of regional autonomy is a must. The DPRD's functions are legislation, budgeting and supervision. The main challenge in carrying out its duties is how the DPRD can create an optimal working mechanism. Raising awareness for the DPRD regarding the functions it carries out is an urgent and important need, because the public really hopes that the DPRD can carry out its parliamentary functions with a more real role and the benefits for the community are felt. The research method is a qualitative method with descriptive analysis. The results of this research are: (1) Optimizing the role of the DPRD in regional autonomy can be realized by carrying out its duties and functions well, so that it can monitor the implementation of development policies carried out by the executive (regional head) so that balance (checks and balances) can be created. between institutions within regional government (2) The DPRD is given the task and authority to form regional regulations together with the regional head. Regional regulation products are one of the tools in carrying out social and democratic transformation, as an embodiment of community culture and regional entities that are able to respond to rapid changes and challenges in the era of autonomy and globalization, as well as creating good local governance as part of sustainable regional development. The conclusions from the research results are: (1) Optimizing the role of the DPRD in regional autonomy can be carried out through the duties and functions of the DPRD as a legislative institution that oversees the running of regional government; and (2) The DPRD's role in administration is to produce legal products, namely regional regulations. Regional regulations regulate various important aspects for the benefit of society so that a good process for forming regional regulations is needed and producing quality regulations.